Functional Regulation of Ginsenosides on Myeloid Immunosuppressive Cells in the Tumor Microenvironment. (November 2019) - Zhang, Yanfei; Qiu, Zhidong; Qiu, Ye; Su, Ting; Qu, Peng; Jia, Ailing
Ginsenosides, the key components isolated from ginseng, have been extensively studied in antitumor treatment. Numerous studies have shown that ginsenosides have direct function in tumor cells through the induction of cancer cell apoptosis and the inhibition of cancer cell growth and enhance the antitumor immunity through the activation of cytotoxic T lymphocytes and natural killer cells. However, little is known about the function of ginsenosides on myeloid immunosuppressive cells including dendritic cells in tumor, tumor-associated macrophages, and myeloid-derived suppressor cells in the tumor microenvironments. Those myeloid immunosuppressive cells play important roles in promoting tumor angiogenesis, invasion, and metastasis. In the review, we summarize the regulatory functions of ginsenosides on myeloid immunosuppressive cells in tumor microenvironment, providing the novel therapeutic methods for clinical cancer treatment.